Environmental Education from the students' knowledge about Sewage Treatment Plant by Root Zone (Research, Society and Development, 2021)
Environmental education, in a formal and non-formal environment, is crucial for promoting environmental awareness in the community. Through actions with scientific dissemination, it can be transformative, impacting economic, social and environmental factors. Regarding issues that affect public health and cause environmental impacts, basic sanitation stands out. In Brazil, part of the population is not assisted by a basic sanitation network, resulting in improper effluents disposal and consumption of untreated water. In this sense, sewage treatment by root zone, as a sustainable alternative, has increasingly demonstrated its effectiveness and low cost of implementation, however it is not well known. Thus, this study aimed to use environmental education to disseminate knowledge about the relevance of sewage treatment by root zone. Initially, an online diagnosis was conducted about the knowledge of effluent treatment with high school students from a public school in Paraná. The results revealed that many of the students were unaware of the root-zone technique, making it difficult to assert the answers. Remarkably, it was realized the great need for the development of educational actions on the topic. Thus, an informative Flyer on the theme was created in order to fill some gaps identified with students. Finally, it is suggested that more Environmental Education actions about this theme be implemented, in the most diverse forms of communication, with a view to scientific dissemination and awareness of the population regarding the importance of the correct treatment of effluents, in favor of the preservation, conservation of the environment and quality of life.